The Impact of Influencer Marketing for Chan 2022 in Forming the Mental Image of the Algerian Tourist Destination: A Field Study of a Sample of Followers of Algerian Influencers - Baout, Lazhar; Maazi, Ghozlane (Journal of Human Sciences, 2023)
This study aimed to find out the effect of influence marketing on improving the mental image of the Algerian tourist destination, and relied on a field study of a deliberate sample of followers of Algerian influencers.The study concluded that there is a significant influence relationship of influence marketing for the year 2022 on improving the mental image of the Algerian tourist destination.